Multiple sclerosis patients valuing their own health status: valuation and psychometric properties of the 15D - Ioannis E. Dagklis; Vasilis H. Aletras; Efthymia Tsantaki; Anastasios Orologas; Dimitrios Niakas (MDPI AG, 2016)
An ongoing debate on decision and cost-utility analyses is whether to use preferences of general public or patients. The aim of this study was to replicate the valuation procedure of the multi-attribute utility generic measure, 15D, using a sample of multiple sclerosis (MS) patients and to assess its psychometric properties. Consecutive outpatient MS patients were recruited from two MS centers in Greece. The three-stage valuation procedure was applied and, with the use of elicited preference weights, an MS patients' algorithm was developed. The original Finnish value set derived from healthy individuals was also used to calculate scores and a comparison between the two algorithms was made. A total of 64 MS patients were evaluated. The 15D scores obtained with the MS patients' valuation algorithm were higher than the original one. The derived utilities differed significantly with respect to age, depressive symptoms, Expanded Disability Status Scale score and clinical form. MS patients indicated as most important domains mobility, mental functioning and vitality. Cronbach's alpha was estimated 0.876 and correlations between relevant dimensions of the instruments were moderate to high. The 15D was generally feasible and reliable in patients with MS and the valuation system yielded acceptable psychometric properties.